KOALISI POLITIK DI INDONESIA PASCA SOEHARTO - Tamma, Sukri; Nadir, Sakinah (Fakultas Ushuluddin dan Filsafat UIN Sunan Ampel Surabaya, 2013)
Political coalitions in the multi-party system was an interesting phenomena in the political studies. Theoretically, political coalitions form were very variatif depending on the reason of the existence, duration, interesting, supporting, as well as the system adopted by the government. All of this depends on the interests of political parties. This paper seeks to answer the questions: first, how do the model of coalition of politics in post-Suharto order; second, how do the trends of coalition in post-Suharto order. Based on a literature review, the results showed: first, basically a political coalition formed after Suharto showed two models, legislative coalition and government coalition. Second, the coalition that occurred in Indonesia today tend to be oriented pragmatic, especially on agreements at the political parties level.